Magnetic properties of as-deposited Fe-Al-O alloy films - Kim, SR; Han, SH; Kim, HJ; Kim, KH; Kim, J (AMER INST PHYSICS, 2000)
The magnetic and structural properties of as-sputtered nanocrystalline Fe-Al-O films, fabricated by a magnetron sputtering apparatus, are investigated as a function of the sputtering input power and the contents of Al and oxygen. A nanocrystalline Fe88.5Al3.5O8.0 film is found to have 4 pi M-s of 18.2 kG, H-c of 0.6 Oe, mu(eff) of 4600 up to 100 MHz. These excellent soft magnetic properties and high frequency characteristics result from nanocrystalline structure, high electrical resistivity, and moderate anisotropy field. These values are sufficient to apply to a high-density recording head. (C) 2000 American Institute of Physics. [S0021- 8979(00)28808-7].